Upaya Pencegahan Bullying Melalui Sosialiasi di Lingkungan Sekolah Melalui Sosialisasi Kolaboratif Berbasis Participatory Action Researchction Research - Fathullah, Amal; Ridani, Muhammad Noor; Suharni, Siti; Hadijah, Siti; Hijriani, Lutfia (Jurnal Dedikasi Pengabdian Pendidikan, 2025)
This community service initiative aimed to prevent bullying at SMP Negeri 1 Halong through a collaborative awareness campaign based on the Participatory Action Research (PAR) approach. The program involved students from UIN Antasari Banjarmasin’s community service program (KKN) and the Legal Aid Institute for Law and Justice Advocacy. Activities included observations, interviews, and socialization sessions with students and teachers. The campaign educated participants on the types, impacts, and legal consequences of bullying, emphasizing respectful peer interaction. Results showed strong student engagement and increased understanding, though ongoing efforts are needed to reduce bullying behavior effectively. Bullying—whether physical, verbal, social, or digital—can severely affect students’ mental health, social relations, and academic outcomes. The project underscores the importance of school-wide collaboration in fostering a safe and inclusive environment. Integrating legal perspectives and educational strategies effectively raised awareness and promoted preventive action.